Pemetaan Prioritas Risiko pada Proyek PT. ABC menggunakan Analytical Hierarchy Process - Renaldy, Richard; Wildan, Wildan; Marpaung, Alfikar; Mohamad, Silvana; Paudi, Yusrin R (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT. ABC, as a contractor engaged in renovation work, faces several operational constraints. This study focuses on determining the priority sequence of renovation project risks using the Analytical Hierarchy Process (AHP) approach. Data collection was conducted through interviews and distributed pairwise comparison questionnaires to experts. From the identification process, ten types of risks deemed critical were recorded. Based on AHP processing, the top three risks requiring attention are Inaccurate Budget Planning (33.12%), Surge in Material Prices (16.94%), and Errors in Material Specifications (14.42%). The Consistency Ratio (CR) value of 0.040 indicates that the assessments provided are consistent. The implication of this study emphasizes financial and technical-material aspects as the most urgent areas requiring immediate attention. The proposed recommendations include improving the cost estimation system and strengthening material supply governance. The results of this study are expected to serve as a reference in formulating mitigation strategies and resource allocation more effectively.